STUDENTS’ INTEREST IN ENGLISH LEARNING THROUGH DUOLINGO APPLICATION - Cindy Paulina Jasandy; Willy Satria; Melvina Melvina (Universitas PGRI Sumatera Barat, 2025)
This study aimed to analyzed students' interest in using the Duolingo app at SMA Negeri 16 Padang. This study used a descriptive qualitative approach, collecting data through structured interviews and video recordings. Participants consisted of 10 students who had been using Duolingo for at least three months. The collected data were analyzed using thematic analysis, following the six stages proposed by Braun and Clarke. The results indicated that students’ interest in learning English was evident in five key indicators: enjoyment, curiosity, attention, active engagement, and self-confidence. In term of enjoyment the app provides an interactive and enjoyable learning environment through gamification features such as daily challenges, points, and levels, which motivate students and increase their engagement. Furthermore, Duolingo fosters students' curiosity, encouraging them to continue learning and improve their English skills. Use of the app also increases students' confidence, particularly in vocabulary and speaking. In conclusion, this study shows that students are indeed interested in learning English using the Duolingo app, as demonstrated by the results of five indicators of student interest in learning. This study recommends integrating Duolingo into English language learning to increase student interest in learning.